Phase I trial of alisertib with concurrent fractionated stereotactic re-irradiation for recurrent high grade gliomas. (March 2019) - Song, Andrew; Andrews, David W.; Werner-Wasik, Maria; Kim, Lyndon; Glass, Jon; Bar-Ad, Voichita; Evans, James J.; Farrell, Christopher J.; Judy, Kevin D.; Daskalakis, Constantine; Zhan, Tingting; Shi, Wenyin
Highlights: Alisertib combined with concurrent fractionated stereotactic radiation therapy (FSRT) is well tolerated for patients with recurrent high grade gliomas (HGG). Clinical outcomes are similar to historical results from alternative treatment options for recurrent HGG. Further exploration combining FSRT with novel systemic therapy agents may provide promising pathways for managing recurrent HGG. Abstract: Background and purpose: We conducted a phase I trial of alisertib, an oral aurora kinase inhibitor, with fractionated stereotactic re-irradiation therapy (FSRT) for patients with recurrent high grade glioma (HGG). Materials and methods: Adult patients with recurrent HGG were enrolled from Feb 2015 to Feb 2017. Patients were treated with concurrent FSRT and alisertib followed by maintenance alisertib. Concurrent alisertib dose was escalated from 20 mg to 50 mg twice daily (BID). Results: 17 patients were enrolled. Median follow-up was 11 months. Median FSRT dose was 35 Gy. There were 6, 6, 3, and 2 patients enrolled in 20 mg, 30 mg, 40 mg, and 50 mg cohort, respectively. Only one DLT was observed. One patient in the 20 mg cohort had severe headache (Grade 3) resolved with steroids. There was no non-hematological grade 3 or higher toxicity. There were two Grade 4 late toxicities (one with grade 4 neutropenia and leukopenia, one with pulmonary embolism). One patient developed radiation necrosis (Grade 3). Sixteen patients finished concurrent treatment and received maintenance therapy (median cycles was 3, range 1–9). OS for all cohorts at 6 months was 88.2% with median survival time of 11.1 months. PFS at 6 months was 35.3% with median time to progression of 4.9 months. The trial stopped early due to closure of alisertib program with only 2 of 3 planned patients enrolled in the 50 mg cohort. Conclusion: Re-irradiation with FSRT combined with alisertib is safe and well tolerated for HGG with doses up to 40 mg BID. Although no DLT observed in the 50 mg cohort, this cohort was not fully enrolled and MTD was not reached. Clinical outcomes appear comparable to historical results. (NCT02186509)